Non-apoptotic cell death associated with perturbations of macropinocytosis - Maltese, William A.; Overmeyer, Jean H. (Frontiers in Physiology, 2015)
Although macropinocytosis is widely recognized as a distinct form of fluid-phase endocytosis in antigen-presenting dendritic cells, it also occurs constitutively in many other normal and transformed cell types. Recent studies have established that various genetic or pharmacological manipulations can hyperstimulate macropinocytosis or disrupt normal macropinosome trafficking pathways, leading to accumulation of greatly enlarged cytoplasmic vacuoles. In some cases, this extreme vacuolization is associated with a unique form of non-apoptotic cell death termed ‘methuosis’, from the Greek methuo (to drink to intoxication). It remains unclear whether cell death related to dysfunctional macropinocytosis occurs in normal physiological contexts. However, the finding that some types of cancer cells are particularly vulnerable to this unusual form of cell death has raised the possibility that small molecules capable of altering macropinosome trafficking or function might be useful as therapeutic agents against cancers that are resistant to drugs that work by inducing apoptosis. Herein we review examples of cell death associated with dysfunctional macropinocytosis and summarize what is known about the underlying mechanisms.